The Relationships among Lecturers’ Performance, Knowledge Management, Budget Planning Models and Innovation: Evidence from Three Universities in Jambi - Fitriaty Fitriaty; Dessy Elliyana; Tona Aurora Lubis (Indonesian Research Journal in Education |IRJE|, 2022)
This study aimed to provide an understanding of knowledge management, budget planning models, lecture performance and innovation at universities in Jambi Province. This study adopted an inferential research design. This study was a cross-sectional survey study. The data were collected from 485 lecturers at 3 universities in Jambi province. This study used a structural equation modeling (PLS-SEM) to analyze the data. The results of this study showed that 1) budget planning models (BPM) affect performance lecturer and innovation, 2) knowledge management affects lecturer performance and innovation, 3) innovation affects lecturer performance, 4) budget planning models affect lecturer performance moderated by innovation, and 5) knowledge management affects the performance of lecturers mediated by innovation. In organizations that place greater emphasis on budgetary objectives by using budget planning models with greater flexibility, it is important to create an enabling atmosphere for leaders of both universities and faculties to maximize the effectiveness of evaluation and monitoring.